Perbandingan Metode Pembelajaran Kontekstual dengan Resitasi terhadap Prestasi Belajar Siswa Pada Mata Pelajaran PAI di Kelas VIII SMP NU Dukuhjati Krangkeng Indramayu - Abas Abdul Jalil (Khulasah : Islamic Studies Journal, 2019)
The formulation of the problem underlying this research is as follows: a) How is the application of contextual learning methods in PAI subjects in class VIII SMP NU Dukuhjati Krangkeng Indramayu? b) How is the application of the recitation learning method in PAI Subjects in class VIII of NU Dukuhjati Middle School Krangkeng Indramayu?, c) What are the student learning outcomes in PAI Subjects in class VIII of NU Dukuhjati Middle School Krangkeng Indramayu?, and d) Between the two methods, Which method has the greatest relationship with students in PAI subjects in class VIII SMP NU Dukuhjati Krangkeng Indramayu? Meanwhile, this research aims to conduct comparative testing experiments on the relationship between contextual learning methods and recitation on student learning achievement in PAI subjects in class VIII SMP NU Dukuhjati Krangkeng Indramayu. This research is included in experimental research and is survey in nature, because the entire number of students in class VIII SMP NU Dukuhjati Krangkeng Indramayu as many as 32 people were sampled. Based on the results of inferential statistical calculations using comparative formulas, it is known that there was an increase in the average score of the experimental class seen from the comparison of the average pretest score of 47.25 while the posttest was 82.87, whereas in the control class the average score of the pretest was 46.87 whereas The posttest score was 61.62, there was no improvement. Furthermore, from the results of independent samples test calculations that the probability value is <0.05 then H0 is rejected, meaning that there is a difference in the increase in student learning outcomes between classes that use the contextual learning method and classes that use the recitation method. Based on the results of the research that has been carried out, several conclusions can be drawn, including: (a) The contextual learning method has a significant effect on increasing the learning achievement of NU Dukuhjati Krangkeng Indramayu Middle School students in class VIII in learning PAI in the odd semester of 2014/2015, and (b) Method Recitation also had a significant effect on improving the learning outcomes of NU Dukuhjati Krangkeng Indramayu Middle School class VIII students in the odd semester of PAI learning in 2014/2015. The different test of the Contextual learning method is significantly different from the Recitation learning method in increasing the learning achievement of NU Dukuhjati Krangkeng Indramayu Middle School students in class VIII in PAI lessons.